2020
DOI: 10.3832/ifor3183-012
|View full text |Cite
|
Sign up to set email alerts
|

Growth dynamics of the Norway spruce and silver fir understory in continuous cover forestry

Abstract: The conversion to uneven-aged, mixed-species stands represents one possible way to mitigate the consequences of disturbances in Norway spruce forests in Central Europe. A better understanding of the establishment and growth dynamics of the understory can contribute to a more effective conversion process. Here we investigate the structure of understory, light climate and growth of natural regeneration of Norway spruce and silver fir in two forest stands undergoing conversion to continuous cover forestry. Stand-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…structure of the selection forest and the related decrease in the diffuse radiation intensity towards the ground created more favourable ecological conditions for the fir trees in the lower layer. The better utilisation of diffuse light by the fir results in its faster growth and, therefore, in the higher competitive ability in comparison with the spruce (Grassi, Giannini 2005;Dănescu et al 2018;Vencurik et al 2019). The deliberate regulation of the light conditions in the lower layer can, thus, to a certain extent affect the changes not only in the structure, but also in the tree species composition of a forest stand (Smith et al 1997;Diaci 2002;Robakowski et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…structure of the selection forest and the related decrease in the diffuse radiation intensity towards the ground created more favourable ecological conditions for the fir trees in the lower layer. The better utilisation of diffuse light by the fir results in its faster growth and, therefore, in the higher competitive ability in comparison with the spruce (Grassi, Giannini 2005;Dănescu et al 2018;Vencurik et al 2019). The deliberate regulation of the light conditions in the lower layer can, thus, to a certain extent affect the changes not only in the structure, but also in the tree species composition of a forest stand (Smith et al 1997;Diaci 2002;Robakowski et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…As the crosssections and cores were taken at a height of 1.3 m, to assess the tree age, it was necessary to add the time needed to reach this height. This period was quantified according to the fitted growth curves of the lower layer trees derived by Vencurik et al (2019) and represented 18 years for the spruce and 16 years for the fir trees. Based on the year ring widths from the collected cores of the spruce and fir trees, the mean annual diameter increment for the period of the last 5 years Δd (diameter increment) was calculated according to the Equation (1):…”
Section: Methodsmentioning
confidence: 99%
“…Light is a key driver shaping species-specific growth trajectories and allocation patterns (Brüllhardt et al 2020). Fir and spruce demonstrate similar plasticity of crown, shoot and needle morphology under changing light conditions (Grassi and Giannini 2005), and trees of both species are capable of surviving under low light intensities (Lundqvist and Nilson 2007;Diaci and Firm 2011;Lin et al 2012;Vencurik et al 2020). Nonetheless, numerous studies have shown that spruce has a greater ability to utilize high-light conditions compared to fir (Grassi and Bagnaresi 2001) and that in conditions close to full light, young spruces grow faster (Brunner 1993;Brunner and Huss 1994) or have similar growth rates as fir (Stanciou and O'Hara 2006).…”
Section: Differences In the Life Histories Of Spruces And Firsmentioning
confidence: 99%
“…Several studies have found that the probability of Norway spruce establishment diminished with increasing overstory density (Schweiger and Sterba 1997;Lin et al 2012;Paluch et al 2021). In smaller gaps or under overstoreys of moderate to high densities, the height growth of spruces is lower than that of firs (Golser and Hasenauer 1997;Stancioiu and O'Hara 2006;Vencurik et al 2020). Dănescu et al (2018) demonstrated that even rapid groupshelterwood cutting regimes with complete canopy removal within two decades still favored fir regeneration.…”
Section: Differences In the Life Histories Of Spruces And Firsmentioning
confidence: 99%
“…The planting of fir in the conditions of full insolation usually does not show a negative influence on the height growth, however, the conditions of the clear-cut area initially contribute to increased mortality and frost injury, and worsened vitality of the young plants (Vaněk, Mauer 2014). Therefore, silver fir is a desirable tree species for https://doi.org/10.17221/178/2022-JFS use in stand reconstructions as underplanting under dying Norway spruce stands (Simon et al 2006;Vencurik et al 2015). The appropriate way may be to plant silver fir in the mixture with rowan tree (Sorbus aucuparia) which offers the desired protective shelter but does not substantially inhibit the growth of fir (Kacálek et al 2023).…”
mentioning
confidence: 99%